The quaternity of learning styles and the Phisca-tawa code in the Inca educational system - Quintanilla Rauch, Carlos (2020)
The educational theory of learning styles seeks to develop meaningful learning in students, to achieve adequate professional skills, being a relevant pedagogical vision in the current educational field. On the other hand, current research is rediscovering the Inca worldview, and allowing the theorizing of a good learning system called in Quechua allinta, based on a code of evaluative principles that allowed training specialists in various fields of knowledge, known as kamayoq. This study allows us to analyze the possible parallelism of current learning styles with the ancient educational worldview of the Incas, because despite referring to different educational contexts, they allowed the achievement of the technical abilities of the Inca kamayoq, similar to the skills of the current professional.